Analysis of Women’s Studies in Management Field: the Brazilian Scientific Production Decade 2000-2010 - de Souza, Eloisio Moulin; Corvino, Marcia de Mello Fonseca; Lopes, Beatriz Correia (Organizações & Sociedade, 2014)
The aim of this paper is a biographical analysis of the scientific publications between the years 2000 to 2010 which had as central theme the feminine and women in six major journals in the field of management in Brazil. The journals surveyed were Cadernos EBAPE, Revista de Administração Contemporânea, Revista de Administração de Empresas, Revista de Administração Mackenzie, Revista Organizações & Sociedade e Revista de Administração da Universidade de São Paulo. They were grouped into three thematic areas, following the criteria of content analysis. It is concluded that most of the articles analyzed approaches of liberal and radical feminist movements. Only one article has proximity to post-structuralism and post-colonialism. However, we cannot say that the articles are ideal representatives of these currents. Finally, there is a lack of research that relate class and race to feminine’s issues, as well studies that search feminine in men.